Advancement of Optical Methods in Experimental Mechanics, Volume 3 : Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics. (2017) - Unknown
No abstract available